PELAYANAN TRANSPORTASI PUBLIK PERUM DAMRI KOTA BANDUNG - Emi Rachmawati (FISIP Universitas Langlangbuana, 2019)
This research is motivated by the decreasing number of public transportation users, in this case Public Corporation DAMRI as a bus service provider in the city. The purpose of this study was to determine how public transportation services Perum DAMRI Bandung. To find out what are the inhibiting and supporting factors in public transportation services DAMRI Bandung City. To find out what efforts are made to minimize the inhibiting factors of public transportation services Perum DAMRI Bandung. The research method used is descriptive qualitative, by collecting data through library research, observation, in-depth interviews and documentation. The results showed that there were several obstacles in the Public Transportation Service of the DAMRI Public Corporation in Bandung. Among others: HR is not ready for innovation, Insufficient welfare for DAMRI officers, Difficult to change the culture of society, DAMRI has not made the community an asset. Efforts are being made to overcome obstacles in the Public Transportation Service in Bandung, among others: Changing the mindset of HR, More concern on employee welfare.